Pengaruh Kelompok Teman Sebaya Terhadap Penentuan Studi Lanjut Siswa - Suwanto, Insan; Istirahayu, Iip; Qonitha, Insiyatun (Counsellia: Jurnal Bimbingan dan Konseling, 2022)
This study was to determine how the friends of the same age level affects to the selection of further studies of high school students in the City of Singkawang. The quantitative research approach with the survey method is used in this study. The instrument of this study was the Peer Scale and the Advanced Study Selection Scale given to 161 high school students in Singkawang City. The data obtained were then analyzed by Descriptive Percentage and simple linear regression analysis assisted by SPSS 24. The results of the descriptive analysis showed that the level of peer influence on students was included in the medium criteria (60%), while the level of selection of further study students was included in the high criteria (74%). Whereas based on the results of simple linear regression that peers significantly influence the selection or determination of further study students (R2 = 0.059, t = 3.154 with a value of sig. 0.002).